Centralization of strategic decisions during the Great Recession: An empirical analysis of European manufacturing firms - Zoltán Bakonyi; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2016)
This study analyzes which types of firm-level shocks were associated with the centralization of strategic decision-making during the recession of 2008-09. We use a unique survey dataset of more than 14000 manufacturing firms from seven European countries which includes direct information on whether the firms centralized or decentralized their strategic decision-making process. Motivated by theoretical approaches claiming that organizations under considerable stress are more likely to centralize, we use multinomial logit models to test whether firms facing a larger fall in turnover, employment, investment or having to postpone their innovations were more likely to change their decision-making process. We find evidence that employment change and postponing innovations are indeed associated with centralization even when we control for ownership, group structure, financing, management, and strategy.
Keywords: M21; D22; D23; 330; centralization; Europe; recessions